ISOLASI RIZOSFER TANAMAN NILAM SEBAGAI AGEN HAYATI TERHADAP Fusarium sp. SECARA IN VITRO - Nisa, Audria Chairun; Ade, Filza Yulina; Lutfia, Anisa (JURNAL BIOSENSE, 2026)
This study aimed to isolate Pseudomonas spp. bacteria from the rhizosphere of patchouli plants (Pogostemon cablin Benth.) at three different location, namely Aceh, Purwokerto, and Pasaman, to test their antagonistic ability in suppressing the growth of Fusarium sp., the fungal pathogen causing root rot in patcouli. Isolation using Pseudomonas Isolation Agar (PIA) medium yielded 40 rhizosphere bacterial isolates, consisting of 14 from Aceh, 16 from Purwokerto, and 10 From Pasaman. Macroscopic morphological identification revealed variations in colony characteristics such as cream/clear color, entire/undulate margins, convex elevation, and viscous/butyrous texture. In vitro antagonism tests via dual culture method on PDA medium were observe twice after 7 and 14 days of incubation, showing strong percentage inhibition of radial growth (PIRG >40%) on day 7 (PW1(2): 42,86%, PW1(3): 65,71%, PW2(3): 57,14%, PW3(1): 54,29%, PW5(2): 48,57% and on day 14 (A1(2): 65%, A2(2): 42,5%, A3(1): 47,5%, PW1(3): 50%, PW2(1): 60%, PW2(3): 55%, PW2(4): 52,5%, PW3(1): 62,5%, PW4(2): 42,5%, PW5(2): 52,5%).